2020 28th International Symposium on Modeling, Analysis, and Simulation of Computer and Telecommunication Systems (MASCOTS) 2020
DOI: 10.1109/mascots50786.2020.9285934
|View full text |Cite
|
Sign up to set email alerts
|

Instability in Geo-Distributed Kubernetes Federation: Causes and Mitigation

Abstract: As resources in geo-distributed environments are typically located in remote sites characterized by high latency and intermittent network connectivity, delays and transient network failures are common between the management layer and the remote resources. In this paper, we show that delays and transient network failures coupled with static configuration, including the default configuration parameter values, can lead to instability of application deployments in Kubernetes Federation, making applications unavail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…), and Ψ j,v = min r∈Γ (Ψ r j,v ), (10) extracting the minimum affinity value among the existing resources, hence considering the most conservative scenario.…”
Section: F Dealing With Multiple Computing Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…), and Ψ j,v = min r∈Γ (Ψ r j,v ), (10) extracting the minimum affinity value among the existing resources, hence considering the most conservative scenario.…”
Section: F Dealing With Multiple Computing Resourcesmentioning
confidence: 99%
“…Indeed, these solutions have been designed for centralized data centers, with guarantees of computing and network resources, and are not designed to identify suitable microservice placement considering their communication patterns. Therefore, they fail to scale on geographically distributed edge-like infrastructures seamlessly, specifically when dealing with nodes that are geographically spread over highlatency WANs [10]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…V. In Sec. VI, we discuss the experimental setup and Several DCI implementations involving IoT deployments 183 emphasised the DCI benefits to Edge computing use 184 cases [6], [7], [8], [9], [10], [11], [12], [13]. The imple-185 mented DCIs in these studies, as shown in Fig.…”
Section: Paper Organizationmentioning
confidence: 99%
“…• Third, despite the efforts toward federated Kubernetes clusters, recent implementations show that Kubernetes federation controllers cannot scale to a sufficient size for Edge computing use cases [9] and can lead to Edge workload deployment instability [10]. Furthermore, Kubernetes-based distributed workload deployments (e.g., multi-cluster and multi-cloud) necessitate the use of additional cluster management tools (e.g., Open Cluster Management 6 ) to automate cluster registration, work distribution, and dynamic policy and workload placement.…”
Section: Paper Organizationmentioning
confidence: 99%